Bioequivalence, Food Effect, and Steady‐State Assessment of Dapagliflozin/Metformin Extended‐release Fixed‐dose Combination Tablets Relative to Single‐component Dapagliflozin and Metformin Extended‐release Tablets in Healthy Subjects - Chang, Ming; Liu, Xiaoni; Cui, Dapeng; Liang, Dan; LaCreta, Frank; Griffen, Steven C.; Lubin, Susan; Quamina‐Edghill, Donette; Boulton, David W. (Clinical therapeutics, 2015)
Simplification of therapeutic regimens for patients with type 2 diabetes mellitus can provide convenience that leads to improved compliance. Dapagliflozin/metformin extended-release (XR) fixed-dose combination (FDC) tablets offer the convenience of once-daily dosing. Two pharmacokinetic (PK) studies were conducted to establish bioequivalence for 2 doses of dapagliflozin/metformin XR FDC versus the same dosage of the individual component (IC) tablets in healthy adults. Two open-label, randomized, 4-period, 4-arm crossover studies were conducted to assess the bioequivalence and PK properties of dapagliflozin and metformin FDCs in healthy subjects under fed and fasting conditions. Participants received single oral doses or once-daily dosing of dapagliflozin/metformin XR (5 mg/500 mg [study 1] or 10 mg/1000 mg [study 2]) for 4 days in an FDC formulation or corresponding strengths of IC tablets. For both of the studies, dapagliflozin and metformin 5 mg/500 mg or 10 mg/1000 mg FDC tablets were bioequivalent to the respective IC tablets. The 90% CIs of the ratio of the adjusted geometric means for all key PK parameters (Cmax, AUC0–T, and AUC0–∞) were contained within the predefined 0.80 to 1.25 range to conclude bioequivalence for both dapagliflozin and metformin. Once-daily dosing to steady state of each FDC tablet had no effect on the PK properties of dapagliflozin or metformin. When the FDCs were administered with a light-fat meal, there was no effect on metformin PK values and only a modest, nonclinically meaningful effect on dapagliflozin PK values. There were no safety or tolerability concerns. Bioequivalence of the FDCs of dapagliflozin/metformin XR and the ICs was established, and no safety issues of clinical concern were raised.